Steal - Patterson, James, 1947-; Roughan, Howard (Grand Central Publishing, 2022)
When the son of the founder of the world's largest hedge fund is thought to have committed suicide, but a body hasn't been found, his father, believing that he is still alive, turns to Dylan Reinhart for help, drawing him into a world of multi-million-dollar secrets and danger.